Sonochemical and mechanical stirring synthesis of liquid metal nanograss structures for low‐cost SERS substrates. (17th May 2018) - Chen, Xiaojun; Chen, Qinnan; Wu, Dezhi; Zheng, Yuekun; Zhou, Zhou; Zhang, Kunpeng; Lv, Wenlong; Zhao, Yang; Lin, Liwei; Sun, Daoheng
Abstract: Micro‐nanofabrication technologies are frequently used to prepare surface‐enhanced Raman scattering (SERS)‐active substrates with specially shaped microstructures, whose characteristics of high sensitivity and good reproducibility are our unswerving pursuit of the goal. However, these techniques suffer from high cost and low throughput, which limits the fabrication of large‐area SERS substrates and restricts their practical application in detection analysis. Therefore, a low‐cost, facile, and environmentally friendly fabrication strategy for SERS‐active substrates by sonochemical treatment in conjunction with mechanical stirring without surfactants is proposed for the detection of low concentrations of molecules. Liquid metal alloys were employed as SERS‐active substrate materials and are easily oxidized to form an oxide film in air, resulting in good dispersion of the nanoparticles. In addition, nanograss consisting of rod‐like structures and nanogaps formed on the micro/nanoparticle surface, providing numerous SERS‐active sites. The shape, size, and surface nanostructure of the micro/nanoparticles could be tuned by controlling the ultrasonication time and the stirring speed. The performance of the SERS substrate coated with Au film was evaluated by using rhodamine 6G as a probe. The resulting limit of rhodamine 6G detection for the optimized nanograss‐structured substrate by Raman analysis was as low as 10 −7  M, and the standard deviation was 8–15.5%, which meets the requirements for the trace detection of analytes. This facile, large‐scale, low‐cost, and green synthesis of a liquid metal nanograss‐structured substrate with high SERS activity and sensitivity makes it a perfect choice for practical SERS detection applications. Abstract : In this study, the first surface‐enhanced Raman spectroscopy investigations, the liquid metal nanoparticles as the surface‐enhanced Raman scattering‐active substrate, were presented. The applied liquid metal nanoparticles synthesized using sonochemical treatment in conjunction with mechanical stirring without surfactants provide significant enhancement of the Raman signal. This phenomenon supplies possibility to perform measurements for the molecular concentration 10 −7 M.